The art of identification : forensics, surveillance, identity - Ferguson, Rex, 1977-; Littlefield, Melissa M., 1979-; Purdon, James, 1983- (AnthropoScene., 2021)
"A multidisciplinary collection of essays exploring current scholarship on the history of human identification. Examines how techniques of identification are entangled within a wider sphere of cultural identity formation"--